2021
DOI: 10.3892/etm.2021.10592
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma‑not always the ‘good guy’: Case report of a life‑threatening basosquamous carcinoma and review of the literature

Abstract: Cutaneous basosquamous carcinoma is a variant of basal cell carcinoma that is characterized by histopathological features of both basal and squamous cell carcinoma. Due to its local invasiveness, high frequency of recurrence, and its metastatic potential, it is considered to be one of the most aggressive subtypes of basal cell carcinoma. We present the case of an 81-year-old male who was admitted to the hospital with incessant hemorrhage arising from a cutaneous tumor that later proved to be a basosquamous car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…BSC is considered an aggressive type of BCC with squamous differentiation. Although it is rare, accounting for 1.2%–2.7% of all non‐melanoma skin tumors, it deserves clinical attention because of its high recurrence rate, potential for metastasis, and poor prognosis 14,15 . Previous studies have reported a metastasis rate of 5%–8.4% and an estimated recurrence rate of 4.5% for BSC compared to conventional BCC, which has a metastasis rate of less than 0.1% 14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BSC is considered an aggressive type of BCC with squamous differentiation. Although it is rare, accounting for 1.2%–2.7% of all non‐melanoma skin tumors, it deserves clinical attention because of its high recurrence rate, potential for metastasis, and poor prognosis 14,15 . Previous studies have reported a metastasis rate of 5%–8.4% and an estimated recurrence rate of 4.5% for BSC compared to conventional BCC, which has a metastasis rate of less than 0.1% 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is rare, accounting for 1.2%–2.7% of all non‐melanoma skin tumors, it deserves clinical attention because of its high recurrence rate, potential for metastasis, and poor prognosis 14,15 . Previous studies have reported a metastasis rate of 5%–8.4% and an estimated recurrence rate of 4.5% for BSC compared to conventional BCC, which has a metastasis rate of less than 0.1% 14,15 . The median survival of patients with BSC metastases is 6.5 years, with an overall 5‐year survival rate of approximately 54% 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BSC accounts for approximately 1% of nonmelanoma skin cancers and frequently occurs in male patients older than 70 years [24]. Pathogenesis is controversial; the origin of BSCs has not yet been fully elucidated, but a high frequency of mutations in the HH pathway has been observed [25].…”
Section: Basosquamous Carcinomamentioning
confidence: 99%